Book review: The Malayan Emergency: Revolution and Counterinsurgency at the End of Empire by Karl Hach - NGOEI, Wen-Qing (WEI Wenqing) (Institutional Knowledge at Singapore Management University, 2025)
This book review critiques the scholarly contributions of historian Karl Hack's new book on the Malayan Emergency.